2021
DOI: 10.1161/circulationaha.120.051828
|View full text |Cite
|
Sign up to set email alerts
|

Microthrombi as a Major Cause of Cardiac Injury in COVID-19

Abstract: Background: Cardiac injury is common in hospitalized patients with COVID-19 and portends poorer prognosis. However, the mechanism and the type of myocardial damage associated with SARS-CoV-2 remain uncertain. Methods: We conducted a systematic pathologic analysis of 40 hearts from hospitalized patients dying of Coronavirus Disease 2019 (COVID-19) in Bergamo, Italy to determine the pathologic mechanisms of cardiac injury. We divided the hearts according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
195
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(237 citation statements)
references
References 22 publications
19
195
1
Order By: Relevance
“…While coronary plaque rupture leading to ST-segment elevation myocardial infarction has been occasionally reported in COVID-19 [130], emerging evidence indicates that microcirculatory derangements may represent a more frequent mechanism of myocardial ischemia. This has been well documented in several histopathological studies demonstrating a high prevalence of microvascular thrombosis, associated with focal areas of necrosis [131,132]. The mechanisms responsible for these alterations are presumably similar to those previously discussed, including coagulopathy, endotheliopathy, and platelet and complement activation [122].…”
Section: Myocardial Ischemic Injurysupporting
confidence: 65%
See 1 more Smart Citation
“…While coronary plaque rupture leading to ST-segment elevation myocardial infarction has been occasionally reported in COVID-19 [130], emerging evidence indicates that microcirculatory derangements may represent a more frequent mechanism of myocardial ischemia. This has been well documented in several histopathological studies demonstrating a high prevalence of microvascular thrombosis, associated with focal areas of necrosis [131,132]. The mechanisms responsible for these alterations are presumably similar to those previously discussed, including coagulopathy, endotheliopathy, and platelet and complement activation [122].…”
Section: Myocardial Ischemic Injurysupporting
confidence: 65%
“…The mechanisms responsible for these alterations are presumably similar to those previously discussed, including coagulopathy, endotheliopathy, and platelet and complement activation [122]. Indeed, a recent study identified a unique composition of COVID-19 associated coronary microthrombi that were significantly enriched in fibrin and terminal complement [131]. These findings provide a pathological basis for the reported occurrence of myocardial infarction with non-obstructive coronary arteries (MINOCA) in COVID-19 patients [130,133].…”
Section: Myocardial Ischemic Injurymentioning
confidence: 52%
“…An additional mechanism of cardiac injury has been described by Pellegrini et al, from the Italian autopsy series. Cardiac myocyte necrosis from microthrombi was different in composition from thrombi from catheter aspirates from patients with acute coronary syndrome [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Troponin T release is commonly seen in critically ill patients because of oxygen supply–demand mismatch and cytokine release, acute heart failure, RV strain (secondary to pneumonia, hypoxia and increased pulmonary artery pressure) and acute arrhythmia [ 10 12 ]. Furthermore, the acute-phase response to severe coronavirus infection can lead to coagulopathy and microvascular thrombosis, for example in the pulmonary and coronary circulations [ 13 , 14 ]. Pre-existing coronary risk factors, such as hypertension and diabetes also predispose patients with COVID-19 to myocardial infarction in the acute setting, possibly implicating it as another potential disease mechanism [ 15 ].…”
Section: Introductionmentioning
confidence: 99%